Scientific and Methodological Basis for Formation of Teachers Working with Students with Disabilities Acquired during Special Military Operations - Kozlovskaya, G.Y.; Prilepko, Yu.V.; Em, E.A.; Demidenko, O.P.; Kolokolnikova, M.V. (Psihologičeskaâ nauka i obrazovanie, 2023)
The article analyzes modern approaches to adult education in the context of preparing teachers to interact with students with disabilities acquired during combat and special military operations. Existing research and teaching methods for people with disabilities do not take into account the specifics of this population. We describied the socio-psychological characteristics of persons with disabilities , affecting the possibilities of adaptation and retraining. We formulated the main areas of necessary changes in educational practice: the formation of motivation for retraining, the creation of a friendly educational environment, the adaptation of the educational process to psychological characteristics of the students and their special educational needs. Emphasis is placed on the methodological aspects of organizing the interaction of teachers and students in the process of professional preparation: the use of pedagogical screening, digital technologies, the gamification method, and the universal design of educational and methodological materials. В статье проанализированы современные подходы к обучению взрослых в контексте подготовки преподавателей к взаимодействию с обучающимися с инвалидностью, приобретенной в процессе боевых действий и специальных военных операций. Выявлено, что существующие исследования и методики обучения лиц с инвалидностью не учитывают специфики данного контингента. Описаны социально-психологические особенности лиц с инвалидностью данной категории, влияющие на возможности адаптации и переобучения. Сформулированы основные области необходимых изменений в образовательной практике: формирование мотивации к переобучению, создание дружелюбной образовательной среды, адаптация образовательного процесса к психологическим особенностям и особым образовательным потребностям. Сделаны акценты на методических аспектах организации взаимодействия преподавателей и обучающихся в процессе профессионального переобучения: использование педагогического скрининга, цифровых технологий, метода геймификации, универсального дизайна учебно-методических материалов.